Simultaneous dual approach in Hawkins type II fractures: Maximum benefit at low risk? - Porta Alesandra, Julieta; Toledo, Ignacio Javier; Vazquez Bestard, Luis Miguel; Catá, Ezequiel; Mazzuchelli, Guilermo Sebastian; Ruiz Navello, Matías Adolfo; Segura, Facundo Manuel; Segura, Florencio Pablo (Journal of the Foot & Ankle, 2025)
Objective: The aim of this study was to evaluate the outcomes of Hawkins type II fractures treated with a simultaneous dual approach. Methods: A retrospective multicenter study was conducted at four major trauma centers. Patients with Hawkins type II closed talar neck fractures managed by a simultaneous dual approach with complete preoperative medical records and a minimum follow-up of six months were included. Results: Eighteen patients were identified. The anatomical reduction was achieved in 17 cases, with a mean follow-up of 53.57 ± 31.77 months (range 8 to 116 months), and the American Orthopaedic Foot & Ankle Society (AOFAS) score was 91.42 ± 7.66 points (range 75 to 100). There were two cases of subtalar arthritis (11%) and two cases of partial avascular necrosis of the talar body (11%), all of them asymptomatic and not requiring secondary surgical procedures up to the latest clinical follow-up. Conclusion: The simultaneous dual approach is a safe and reliable strategy for managing Hawkins type II talar neck fractures without significantly compromising the talar circulation. We recommend that future prospective studies with a larger sample be conducted to validate these findings further. Level of evidence IV; Therapeutic studies; Case series.